In vivo Raman spectroscopy–assisted early identification of potential second primary/recurrences in oral cancers: An exploratory study. Issue 11 (24th July 2017) - Malik, Akshat; Sahu, Aditi; Singh, S. P.; Deshmukh, Atul; Chaturvedi, Pankaj; Nair, Deepa; Nair, Sudhir; Murali Krishna, C.
Abstract: Background: Higher rates of local recurrences and second primaries, ascribable to field cancerization, are known problem in oral cancers. The present study explored utility of identification of potential recurrences by Raman spectroscopy, which has been shown to identify oral precancers, cancers, and field cancerization in humans and micro‐sized mechanical irritation‐induced tumors in animals. Methods: Raman spectra were acquired from tumor and contralateral normal mucosa in 99 patients with oral cancer who were then followed up for appearance of clinically apparent cancerous lesions. Misclassifications observed in subsequent multivariate statistical analysis between contralateral normal and tumor spectra were correlated with appearance of new malignant lesions. Results: The patients with mismatched spectra had 1.5 times higher chances of developing local recurrence. The sensitivity of Raman spectroscopy in predicting the recurrences was 80% and the specificity was 29.7%. Conclusion: Findings provide proof‐of‐concept for Raman spectroscopy‐based identification of sites that have higher propensity to progress to carcinomas before becoming clinically apparent. Prospective validation of Raman spectroscopy by including additional oral cavity subsites and use of multifiber bundles may improve rate of identification of recurrence‐prone subjects.